2016
DOI: 10.1146/annurev-environ-110615-090000
|View full text |Cite
|
Sign up to set email alerts
|

Can We Tweet, Post, and Share Our Way to a More Sustainable Society? A Review of the Current Contributions and Future Potential of #Socialmediaforsustainability

Abstract: Social media is changing how people connect, create, and share content and is an integral force shaping modern society. Given the significant environmental challenges society faces, this review considers (a) how social media is currently contributing to the development of a more sustainable society and (b) directions for future work such that researchers and practitioners may more effectively utilize this technology. At present, case studies, anecdotal evidence, and research demonstrate that social media is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 110 publications
(112 reference statements)
1
45
0
5
Order By: Relevance
“…These types of questions have relevance beyond pangolins (see e.g. Pearson et al 2016;Wu et al 2018), but high profile issues that have evolved over time (in terms of media and public interest), such as pangolin trade, will likely offer useful case studies.…”
Section: Discussionmentioning
confidence: 99%
“…These types of questions have relevance beyond pangolins (see e.g. Pearson et al 2016;Wu et al 2018), but high profile issues that have evolved over time (in terms of media and public interest), such as pangolin trade, will likely offer useful case studies.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the different and sometimes less rigorous ways of naming the relationship between activism mediated by digital technologies and education, the literature review revealed a broad set of political practices which involve different levels of participation: critical and active media consumption, searching for and circulating information, coordination of actions, content production, hacker practices. Likewise, in the different texts, activism mediated by digital technologies (or this concept referred to with different terms) is associated with various forms of technological appropriation that have diverse practices and purposes: raising awareness, protesting or defending certain causes of interest, promoting social mobilization, creating new forms of citizen participation, generating local, national and global collaboration networks, and strengthening solidarity and a sense of community (Pearson et al, 2016;Linder et al, 2010;Khoury-Machool, 2007;Theocharis, 2012;Peña, Rodríguez, & Sáez 2016;Enguix, 2016;González-Lizarraga, Becerra-Traver, & Yanez-Díaz, 2016;Vivitsou & Viitanen, 2015;Weeks, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The newest social movements usually are organized around plural motivations linked to diverse sources of indignation: imposed educational reforms (Bekkers et al, 2011); sexual violence; discriminatory policies and the need for a better sex education policy (LaRiviere et al, 2012;Linder et al, 2010;Shayne, 2008); abduction and violation of the right of women to formal education (Chiluwa & Ifukor, 2015); job insecurity (Biddix & Park, 2008); defense of high quality public education (Valenzuela, 2013;Theocharis, 2012;Heron-Hruby & Landon-Hays, 2014;Fullam, 2017); genocide or extreme violence (Biddix, 2010); environmental damage and animal abuse (Pearson et al, 2016;Weeks, 1999), to name a few.…”
Section: Activism and Its Relationship With The Field Of Educationmentioning
confidence: 99%
See 2 more Smart Citations